The Role of Emergency Pleural Drainage in the Obstructive Shock in a Left Massive Hemothorax: A Case Report - Lainy, Krisdianto Putra; Saputra, Charles; Bria, Januario; Wijaya, Oka; Chaerunnisa, Afina; Alvarabie, Radietya (Respiratory Science, 2024)
Background: Spontaneous hemothorax is much less common, and the causes include malignancies, anti-coagulant medications, vascular ruptures, endometriosis, pulmonary infarctions, adhesions with pneumothorax, and hematologic abnormalities such as hemophilia. This report presented a confirmed case of obstructive shock in a patient with massive left hemothorax and elaborated on the role of emergency pleural drainage in this particular clinical situation. Case: Reported a case of a 56-year-old man with a 2-month history of dyspnea, leg swelling, abdominal bloating, hemoptysis, and fatigue. Physical examination revealed an asymmetrical chest wall expansion with a predominance of abdominal breathing. His neck and face were markedly discolored and swollen, with distended veins. The left hemithorax was dull on percussion and, on auscultation, significantly reduced air entry at the left lung base. Discussion: The patient was given an O2 non-rebreathing mask (NRBM) on arrival. The patient was administered two vasopressors (dopamine, 2.5 mcg/kg per body weight/minute, and norepinephrine, 0.1 mcg/kg per body weight/minute). Given the patient’s hemodynamic instability and high probability of imminent death. The patient required urgent intervention to relieve the obstructive shock. The surgical department was inserted to treat the massive hemothorax, which drained approximately 1.5 liters of blood. The patient received supplementary oxygen, antibiotics, and furosemide. Conclusion: The pleural fluid drainage alleviated the dyspnea. As supportive therapy, the patient received oxygen, antibiotics, and furosemide. On the follow-up, the mediastinal shift had resolved simultaneously.